FDA Accelerated Approval of Pembrolizumab for Recurrent Locally Advanced or Metastatic Merkel Cell Carcinoma. (28th April 2020) - Bradford, Diana; Demko, Suzanne; Jin, Susan; Mishra‐Kalyani, Pallavi; Beckles, Aaliyah R.; Goldberg, Kirsten B.; Lemery, Steven; Ward, Ashley; Keegan, Patricia; Pazdur, Richard
Abstract: : On December 19, 2018, the Food and Drug Administration granted accelerated approval to pembrolizumab (KEYTRUDA, Merck & Co. Inc., Whitehouse Station, NJ) for adult and pediatric patients with recurrent locally advanced or metastatic Merkel cell carcinoma (MCC). Approval was based on Cancer Immunotherapy Trials Network protocol 9, also known as KEYNOTE‐017 (NCT02267603), a multicenter, nonrandomized, open‐label trial that enrolled 50 patients with recurrent locally advanced or metastatic MCC who had not received prior systemic therapy for their advanced disease. The major efficacy outcome measures were overall response rate (ORR) and response duration assessed by blinded independent central review per RECIST 1.1. The ORR was 56% (95% confidence interval: 41, 70) with a complete response rate of 24%. The median response duration was not reached. Among the 28 patients with responses, 96% had response durations of greater than 6 months and 54% had response durations of greater than 12 months. The most common adverse reactions of pembrolizumab reported in at least 20% of patients who received pembrolizumab as a single agent were fatigue, musculoskeletal pain, decreased appetite, pruritus, diarrhea, nausea, rash, pyrexia, cough, dyspnea, constipation, pain, and abdominal pain. Implications for Practice: This report presents key information on the basis for the Food and Drug Administration's accelerated approval of pembrolizumab for the treatment of recurrent locally advanced or metastatic Merkel cell carcinoma, including efficacy and safety information. This approval provides patients and physicians with an additional treatment option for this aggressive and life‐threatening carcinoma. Abstract : This report summarizes key information on the basis for the accelerated approval of pembrolizumab for the treatment of recurrent locally advanced or metastatic Merkel cell carcinoma.